The Influence of Earning Per Share and Dividend Per Share on the Share Price of PT Adaro Energy, Tbk for the 2013 - 2022 Period - Suraya, Amthy; Rismanty, Vidya Amalia; Maya, Dinda Eka (Formosa Journal of Sustainable Research, 2024)
This research aims to determine the influence of EPS and DPS on the share price of PT Adaro Energy, Tbk for the period 2013 - 2022, partially or simultaneously. The sample selection was carried out using a purposive method, namely companies that distributed dividends for 10 consecutive years for the period 2013 - 2022, so that the financial reports of PT Adaro Energy, Tbk were obtained. The analytical method used in this research is multiple linear regression analysis, Adjusted R2, t test and f test with the SPPS Version 27 application. Research shows that several Earning Per Shares have a calculation of -1.610 (<2.36462) with a probability value of 0.151 so that the variable EPS does not have a significant influence on share prices. DPS has a calculation of 3.227 (<2.36462) with a probability value of 0.015 so that partially Dividend Per Share has a significant negative influence on share prices. Meanwhile, Earning Per Share and Dividends Per Share have a calculated total of 9,959 (>4.46) with a probability value of 0.010, which means that together Earning Per Share and Dividends Per Share have a significant effect on share prices